Commercialization of Higher Education, Challenges of Education System in the Era of Technology 4.0 - Andi Irlina; Muhammad Iqbal Noor; Elli Elli (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
Commercialization of Higher Education has become an increasingly dominant issue in the educational system in the era of Technology 4.0. This article attempts to identify the changes in the higher education paradigm caused by commercialization, including rising educational costs, profit, and influence on the curriculum. Additionally, the article examines the impact of commercialization on higher education, the challenges it faces, and ways to overcome the existing barriers. The research conducted a literature review. The writer uses documents such as journals, books, and online media as data sources. The collected data was analyzed using content analysis methods. This research reveals that the commercialization of education is a deliberate system created by both governments and investors. The government minimizes the government budget expenses by changing PTN to PTN-BH. At the same time, the investors try to optimize their profits from educational institutions without considering the achievement of educational goals. On the other hand, the commercialization of education reflects that education is treated as a commodity. However, it must be acknowledged that the commercialization of education has both positive and negative impacts. Therefore, efforts to mitigate the commercialization of education that can serve as a solution are needed. In this regard, the government, as the education decision maker, must regulate higher education quality and ensure broader accessibility. This requires a balanced approach between the commercial needs of universities and the interests of the public in providing quality education. Additionally, higher education must continue adapting to Technology 4.0 to maximize the potential for more inclusive and relevant education while maintaining the integrity of education and Islamic values.